2020
DOI: 10.1007/s10029-020-02227-1
|View full text |Cite
|
Sign up to set email alerts
|

A manual reduction of hernia under analgesia/sedation (Taxis) in the acute inguinal hernia: a useful technique in COVID-19 times to reduce the need for emergency surgery—a literature review

Abstract: Background Acute IH is a common surgical presentation. Despite new guidelines being published recently, a number of important questions remained unanswered including the role of taxis, as initial non-operative management. This is particularly relevant now due to the possibility of a lack of immediate surgical care as a result of COVID-19. The aim of this review is to assess the role of taxis in the management of emergency inguinal hernias. Methods A review of the literature was undertaken. Available literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 14 publications
1
24
0
2
Order By: Relevance
“…De Simone et al [ 20 ] reported that non-operative approach can be applied acute appendicitis, acute cholecystitis, adhesive small bowel obstructions and incarcerated hernias in pandemic period. East et al [ 21 ] reported that the use of taxis procedure (a manual reduction of hernia under analgesia/sedation) for incarcerated inguinal hernia is a useful first-line treatment in situations where surgical care is not immediately available, including the COVID-19 pandemic. In this study, there was a severe decrease in the number of these patients who were recommended nonoperative follow-up in recent publications during pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…De Simone et al [ 20 ] reported that non-operative approach can be applied acute appendicitis, acute cholecystitis, adhesive small bowel obstructions and incarcerated hernias in pandemic period. East et al [ 21 ] reported that the use of taxis procedure (a manual reduction of hernia under analgesia/sedation) for incarcerated inguinal hernia is a useful first-line treatment in situations where surgical care is not immediately available, including the COVID-19 pandemic. In this study, there was a severe decrease in the number of these patients who were recommended nonoperative follow-up in recent publications during pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Manual reduction is standard treatment for incarcerated inguinal hernia in children. Moreover, this technique is very useful to decrease the need for any emergency procedure during the COVID-19 pandemic [ 7 ]. However, manual reduction is not without some risks.…”
Section: Discussionmentioning
confidence: 99%
“…De Simone et al [11] reported that non-operative treatment could be applied in acute appendicitis, acute cholecystitis, adhesive bowel obstructions, and incarcerated hernias in the period of the pandemic. East et al [12] reported that a manual reduction of incarcerated hernias under analgesia or sedation is a useful rst treatment in situations where surgical management is not immediately available, including the Covid-19 pandemic. Simultaneously, a reasonable decrease in road tra c accidents was encountered due to the population's tra c limitations.…”
Section: Discussionmentioning
confidence: 99%